The Influence of Local Own Revenue Funds, Tax/Non-Tax Profit Sharing, Special Allocation Funds, Others Legal Income and Operational Expenditures on Regional Financial Performance in Jambi Province - Mulia, Denni Indra; Mukhzarodfa, Mukhzarodfa (The International Journal of Business Review (The Jobs Review), 2020)
This study aims to see and analyze whether Local Own Revenue, Tax/Non-Tax Profit Sharing, Special Allocation, Others Legal Income Funds, and Operational Expenditures partially and simultaneously affect the regional financial performance. This research was conducted in Jambi Province using secondary data obtained and endorsed by the Regional Financial Management Agency of Jambi Province in the form of a Jambi Provincial Government Financial Budget Realization Report Document. The data were analyzed by the statistical analysis method using the IBM SPSS Statistics 25 program. It was analyzed using multiple linear regression analysis models, namely pooled data from 2007 to 2019. The results of the study through the F statistical test showed that there was an influence between the independent variables on the three dependent variables with a value of 6.98, 8.28, 8.9 greater than F table 3.20. The R Square (R2) test shows the values of 0.832, 0.873, 0.865 indicating that the correlation or relationship between the dependent variable (Y) and the independent variable is quite strong. The t table test is 2.262. The results showed that partially the original regional income has a positive and significant effect on the financial performance of local governments by using the degree of fiscal decentralization indicator and routine capability index, for the Conformity ratio has a negative but significant effect with value 3.208, 3.414 dan 2.737. Tax/Non-Tax Profit Sharing Funds have a positive and significant effect on Regional Government Financial Performance by using the Routine Capability Index with value 2.438. The Special Allocation Funds have a positive and insignificant effect on the Financial Performance of Regional Governments by using the Degree of Fiscal Decentralization indicator with value 2.753. Other Legal Income funds have a negative and significant effect on the financial performance of local governments by using the Conformity ratio with a value of 4.470.